Srebrna ptica izpod Jalovca - Košir, Uroš (Zgodovinski časopis, 2025)
This article examines the fate of the crew and that of the American bomber Consolidated B-24G Li-berator 42-78259, which crashed on 22 November 1944 in the area of Kotovo Sedlo under Jalovec. Based on archival sources, post-war records, eyewitness testimonies, and fi eld research, the fate of the crashed plane and crew members, who pa-rachuted out of the falling plane, was investigated and reconstructed. Newly acquired data present a diff erent picture than that previously known from post-war records and stories circulating among the locals of the Upper Sava Valley.
Keywords: American airmen; ameriški letalci; aviation; bomber; bombnik; Consolidated B-24G Liberator; druga svetovna vojna; letalstvo; vojni zločinci; war crimes; World War II